Coworker support, work–family conflict, job satisfaction, and turnover intention: female employees in post-organizational socialization - Yang Bai; Jinquan Zhou (Frontiers in Psychology)
This study extends the concept of organizational socialization from coworker support to its impact on shaping work–family conflict (WFC), job satisfaction, and turnover intention. Utilizing a sample of 413 female casino dealers, it investigates the interplay between coworker support, WFC, job satisfaction, and turnover intention among female employees in the Macau casino industry, focusing on the post-organizational socialization phase. The results indicate that support from coworkers significantly decreases WFC and improves job satisfaction. Both factors mediate the relationship between coworker support and turnover intention. Furthermore, WFC positively impacts turnover intention, while job satisfaction has a negative impact. These findings highlight the importance of casino management fostering supportive coworker relationships to improve job satisfaction and employee retention, thus enhancing the effectiveness of organizational socialization. This study contributes to the organizational socialization theory and provides practical implications for managing female employees in high-pressure environments.